1α, 25‐dihydroxyvitamin D3 supplementation alleviates perfluorooctanesulfonate acid‐induced reproductive injury in male mice: Modulation of Nrf2 mediated oxidative stress response. Issue 2 (2nd November 2022) - Liang, Yongchao; Lu, Jingjing; Yi, Wenjie; Cai, Ming; Shi, Weiqiang; Li, Bingyan; Zhang, Zengli; Jiang, Fei
Abstract: Perfluorooctanesulfonate acid (PFOS) is a typical persistent organic pollutant that widely exists in the environment. To clarify the toxic effects and mechanisms of PFOS and to find effective intervention strategies have been attracted global attention. Here, we investigated the effects of PFOS on the male reproductive system and explored the potential protective role of 1α, 25‐dihydroxyvitamin D3 (1α, 25(OH)2 D3 ). Our results showed that 1α, 25(OH)2 D3 intervention significantly improved PFOS‐induced sperm quality decline and testicular damage. Moreover, 1α, 25(OH)2 D3 aggrandized the total antioxidant capacity. Furthermore, after PFOS exposure, the transcription factor nuclear factor erythroid‐related factor 2 (Nrf2) was adaptively increased together with its target genes, such as HO‐1, NQO1, and SOD2. Meanwhile, 1α, 25(OH)2 D3 ameliorated PFOS‐induced augment of Nrf2 and target genes. These findings indicated that 1α, 25(OH)2 D3 might attenuate PFOS‐induced reproductive injury in male mice via Nrf2‐mediated oxidative stress.